1995
DOI: 10.1093/nar/23.6.1003
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of RNA-primed DNA synthesisin vitroby DNA polymerase α-primase

Abstract: The initiation of new DNA strands at origins of replication in animal cells requires de novo synthesis of RNA primers by primase and subsequent elongation from RNA primers by DNA polymerase alpha. To study the specificity of primer site selection by the DNA polymerase alpha-primase complex (pol alpha-primase), a natural DNA template containing a site for replication initiation was constructed. Two single-stranded DNA (ssDNA) molecules were hybridized to each other generating a duplex DNA molecule with an open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…DNA pol ␣/primase acts by first adding the eventual second nucleotide of the RNA sequence, preferring this nucleotide to be a purine. More recently, a preferential priming sequence 5Ј-d(GCTTTCTTCC) has been deduced in vitro (20).…”
Section: Resultsmentioning
confidence: 99%
“…DNA pol ␣/primase acts by first adding the eventual second nucleotide of the RNA sequence, preferring this nucleotide to be a purine. More recently, a preferential priming sequence 5Ј-d(GCTTTCTTCC) has been deduced in vitro (20).…”
Section: Resultsmentioning
confidence: 99%
“…Primase initiates synthesis by insertion of the first 5Ј-GTP at nucleotide 31. Nucleotide 23 is seven nucleotides from the initiation start site (16). These two positions were selected to test for differences in primer synthesis that might relate to the position of araCMP within the priming site.…”
Section: Insertion Of Aracmp Into Full-lengthmentioning
confidence: 99%
“…Primer initiation sites are rich in thymidine and cytosine residues (13,15,16,26). The high level of thymidine residues should make it more likely that FaraAMP and araAMP might be incorporated into elongating primers by primase within the first 6 bases, resulting in truncated primers that are not elongated by pol ␣.…”
Section: Insertion Of Aracmp Into Full-lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect that this result may be related to the extent of unwinding that takes place in the two reactions. For instance, it has been reported that the priming sites nearest a given replication fork are preferentially used (36). Walter and Newport discuss additional evidence that the DNA Pol ␣-primase complex specifically binds to forks formed during DNA unwinding (80).…”
Section: Vol 75 2001 Replication Initiation Site Selection In Vitromentioning
confidence: 99%